Antonin Artaud's Alternate Genealogies : Self-Portraits and Family Romances - Stout, John Cameron (Book collections on Project MUSE., 1996)
In Antonin Artaud's Alternate Genealogies Stout analyzes two separate but interrelated preoccupations central to Artaud's work: the self-portrait and the family romance. He shows how Artaud, in several important but relatively neglected texts, rewrites the life stories of historical and literary figures with whom he identifies, including Paolo Ucello, Abelard, Van Gogh and Shelley's Francesco Cenci, in an attempt to reinvent himself through the image, or life, of another. Throughout the book Stout focuses on Artaud's struggles to recover the sense of self that eludes him and to master the reproductive process by recreating the family in - and as - his own fantasies of it.